2021
DOI: 10.1186/s12934-021-01661-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant protein production provoked accumulation of ATP, fructose-1,6-bisphosphate and pyruvate in E. coli K12 strain TG1

Abstract: Background Recently it was shown that production of recombinant proteins in E. coli BL21(DE3) using pET based expression vectors leads to metabolic stress comparable to a carbon overfeeding response. Opposite to original expectations generation of energy as well as catabolic provision of precursor metabolites were excluded as limiting factors for growth and protein production. On the contrary, accumulation of ATP and precursor metabolites revealed their ample formation but insufficient withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…This accumulation is probably due to the high energy demand imposed to the cell for the synthesis of the recombinant protein. Recently, it has been demonstrated that this ‘‘metabolic burden’’ is not caused by energy limitation; on the contrary, this is due to restrictions in anabolic functions (Weber et al, 2021 ). This energy excess due to RPP causes a reduction of catabolic carbon processing, hence, (i) affecting negatively the growth rate; (ii) enhancing acetate formation, and (iii) reducing the carbon substrate uptake, evidenced by the accumulation of glucose (Weber et al, 2002 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This accumulation is probably due to the high energy demand imposed to the cell for the synthesis of the recombinant protein. Recently, it has been demonstrated that this ‘‘metabolic burden’’ is not caused by energy limitation; on the contrary, this is due to restrictions in anabolic functions (Weber et al, 2021 ). This energy excess due to RPP causes a reduction of catabolic carbon processing, hence, (i) affecting negatively the growth rate; (ii) enhancing acetate formation, and (iii) reducing the carbon substrate uptake, evidenced by the accumulation of glucose (Weber et al, 2002 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptomic response towards recombinant protein production was also mainly characterized by a vanishing influence of CRP-cAMP and an increasing influence of phosphorylated ArcA [25]. Energy-limiting conditions were also not detected, on the contrary, induced recombinant protein production was also initially accompanied by elevated ATP levels and an elevated adenylate energy charge [15,64]. Recent experiments corroborated that interference of recombinant protein production with normal host cell metabolism is not the result of competition for energy and precursor metabolites but mainly an inhibitory effect of toxic amounts of recombinant mRNA on well organized and structured anabolic processes which are needed for cell growth [68][69][70][71].…”
Section: Similar Transcriptome Changes Occur In Response To Induced R...mentioning
confidence: 99%
“…The reduction of respiratory activity and continued uptake of glucose leads to accumulation of metabolites and forces carbon flow towards side reactions, e.g., to acetate, the most prominent overflow metabolite of E. coli but also to less energy efficient pathways such as the methyl-glyoxal pathway [58]. As the initial metabolic responses occur immediately after the glucose pulse they are certainly also regulated at the allosteric level of enzyme activity through accumulating metabolites auch as ATP, fructose-1,6-bisphosphate and pyruvate (please refer also to [20] for additional data and [64] for discussion). These initial responses towards glucose excess can reduce respiratory energy generation but they are not sufficient to lead to balanced catabolic and anabolic carbon processing.…”
Section: Other (More Delayed) Changes Of Catabolism In Response To Gl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of so many alternative expression systems, there is no guarantee that every type of protein will have a high yield or catalytic/functional activity. The occurrence of these phenomena can be attributed to two main aspects: (i) the host burden caused by the massive production of RPs [16] and (ii) the limited post-translational modification (PTM) capacity and generation of inclusion bodies (IBs) [17]. In fact, any production of RPs, especially toxic proteins, will inevitably compete with the host for resources, which are mainly reflected in the additional DNA replication burden, competition for transcription-and translation-related elements (RNAP, ribosomes, tRNA, and amino acids), and the additional energy and substrates consumed by PTMs [18].…”
Section: Introductionmentioning
confidence: 99%